A evolução social e política proposta por Justo Sierra para o México (1900-1911) - Santos, Luciano Rodrigues (2017)
The present study examines the performance of Mexican essayist and intellectual Justo Sierra Méndez (1848-1912), in the project of problematization and defense of a mestizo identity for Mexico in the late nineteenth century. The main point of the research is to analyze the categories listed by Sierra in his essays, starting from the assumptions of Cultural History, in order to systematize and provide the debate on mestizaje, identity and politics in nineteenth century Mexico. Therefore, the purpose of this study is to examine Sierra's thinking regarding the multicultural formation of the Mexican nation amid the social and political problems that besieged social thought in that country between the nineteenth and early twentieth centuries.